2022
DOI: 10.3390/molecules27228108
|View full text |Cite
|
Sign up to set email alerts
|

Control Efficacy of Salicylic Acid Microcapsules against Postharvest Blue Mold in Apple Fruit

Abstract: Salicylic acid (SA) is a natural inducer of disease resistance in fruit, but its application in the food industry is limited due to low water solubility. Here, SA was encapsulated in β-cyclodextrin (β-CD) via the host–guest inclusion complexation method, and the efficacy of SA microcapsules (SAM) against blue mold caused by Penicillium expansum in postharvest apple fruit was elucidated. It was observed that SAM was the most effective in inhibiting the mycelial growth of P. expansum in vitro. SAM was also super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…SA treatment of apple fruits before inoculation with P. expansum effectively inhibited blue mold [184]. SA increases resistance to P. expansum by increasing SOD activity [185]. Methyl salicylate (MeSA) vapors increased epicatechin, PAL, chitinase, β-1,3-glucanase activity and reduced anthracnose of avocado significantly [186].…”
Section: Plant Growth Regulators (Pgrs)mentioning
confidence: 99%
“…SA treatment of apple fruits before inoculation with P. expansum effectively inhibited blue mold [184]. SA increases resistance to P. expansum by increasing SOD activity [185]. Methyl salicylate (MeSA) vapors increased epicatechin, PAL, chitinase, β-1,3-glucanase activity and reduced anthracnose of avocado significantly [186].…”
Section: Plant Growth Regulators (Pgrs)mentioning
confidence: 99%
“…SA has been applied as a postharvest treatment to enhance disease resistance in fruits. Studies have shown that SA treatment can reduce postharvest decay caused by pathogens such as P. expansum in apples, peach, and citrus fruits . Biochemical preservatives such as methyl salicylate, methyl jasmonate, and melatonin can also control postharvest diseases of fruits …”
Section: Biological Controlmentioning
confidence: 99%
“…An important process of cyetpyrafen formulation application involves interfacial transfer, specifically the process of droplets falling onto leaves, and adhering and permeating the leaf surface [22]. The contact angle is the most direct indicator of wetting and spreading properties.…”
Section: Influence Of the Size Effect On The Contact Anglementioning
confidence: 99%